The Impact of Quality Indicators Towards Student Satisfaction in Higher Education - Ahmad, Md. Fauzi; Mohd Razaki, Nur Aesyah; Ahmad, Ahmad Nur Aizat (Research in Management of Technology and Business, 2021)
Higher education institutions are important to deliver students’ relevant knowledge and skills for future carrier. The current issues are inequality of service quality amongst Malaysia universities. Quality indicators are used to determine students’ satisfaction data based on the service quality experiences. Low students’ satisfaction contribute to lower students’ performance and hardly to fit into current employment market. This research focuses on the relationship between quality indicators of service quality provided by UTHM and students’ satisfaction. Collection of the data was done by distributing questionnaires to 100 respondents from undergraduates of fourth year students among six faculties. The sampling techniques was stratified sampling method. The result showed that each of the quality indicators has positively impact on students’ satisfaction. Extracurriculum activities are the most influencing indicator in this study toward the students’ satisfaction. Furthermore, only field and faculty have impacts toward satisfaction amongst students. This study was to evaluate the current level of service quality in UTHM in students’ viewpoint for future improvement in providing a better learning environment.